Effect of the Incorporation of an Innovative Monomer with a Quaternary Ammonium Group into a Temporary Soft Liner on Its Biological and Physicochemical Properties - Patrycja Kula; Izabela Barszczewska-Rybarek; Anna Mertas; Grzegorz Chladek (Molecules)
The colonizing of temporary soft lining materials in the oral cavity by yeast-like fungi, particularly Candida albicans, poses a significant risk of complications during prosthetic treatment. Various experimental materials incorporating antimicrobial additives, such as drugs, natural oils, and inorganic particles, have been tested. However, these components are not chemically bonded to a polymer network, making them prone to being easily released into the surrounding environment. This study aimed to evaluate experimental soft lining materials containing liquid components with 2-(methacryloyloxy)ethyl-2-decylhydroxyethylmethylammonium bromide, a monomethacrylate monomer with a quaternary ammonium group, added at concentrations of 8.54%, 8.75%, and 14.90% by weight. The adherence of Candida albicans, cytotoxicity, glass transition temperature (Tg), sorption (WS), solubility (WSL), Shore A hardness (SHA), tensile strength (TS), and tensile bond strength (TBS) were tested. Two tested materials did not show cytotoxicity for the 2-day undiluted extracts. The Candida albicans adhesions were reduced for two materials. The SHA values compared to the control were varied but all decreased with time. WS and WSL increased compared to the control. The TBS values were at an acceptable level.